Transformation of the role of local budgets income as an instrument of budget mechanism in the context of decentralization - KRUPKA, Mykhailo; KULCHYTSKY, Myroslav; KOVALENKO, Viktor (Scientific journal «World of Finance», 2019)
Introduction. In the conditions of the transformational changes in the national economy, there is a need for modernization of the formation and strengthening of the financial base of local authorities, which are subject to the exercise of powers in accordance with the current legislation of Ukraine. And the very financial decentralization to date allows solving the problematic issues of ensuring the current needs of local self-government bodies, and hence the increase of local budget revenues and the sustainable development of territorial communities. Among the main tasks of the reform of decentralization of the budget system it is an increase in the financial capacity of local self-government and capacity building. At present, financial decentralization is one of the key instruments provided to local self-government in order to implement the strategy of socio-economic development of territories. By providing a significant portion of the financial resources to local self-government, in particular the united territorial communities, the government delegated some of the authority to local councils that are responsible for the management decisions made and the rational use of budget funds. The purposeof the article is to assess the role of local budget revenues as an instrument of the budget mechanism, monitoring their formation and transformation in the context of fiscal decentralization. Results. It has been established that decentralization is necessary to maximally approximate the provision of public services to the population, to improve the management system, to increase the efficiency of problem solving, transmitted to the local level. Financial decentralization reflects the urgent need to ensure the independence of local self-government bodies. The changes made to the Budget and Tax Codes of Ukraine concerning the allocation of local budgets by sources of income are considered. A new model of intergovernmental relations, which provides incentives for local authorities, is outlined. An analysis of the dynamics and structure of local budget revenues for 2013-2017 has been made, which allowed to establish the strengthening of their role as a tool of the budgetary mechanism, taking into account changes that have taken place in the context of decentralization. The features of the new model of intergovernmental relations are considered and the proposals on the formation of the revenue base of local budgets in the context of decentralization are substantiated. Conclusions. As a result of the research, it was found that in order to increase local budget revenues it is expedient to: ensure effective interaction between state authorities, local self-government, private entities and civil society institutions; to improve the mechanism of attraction and use of international technical assistance, financial resources of international financial organizations for the support of regional development; to identify and realize the hidden and underestimated development potential of each region, district, united territorial community; to raise the level of entrepreneurial initiative, use of business opportunities and the level of investment attractiveness in order to implement investment projects; to introduce self-regulation by local government tax rates for real estate and land, as well as providing incentivesfor their payment.